Analisis Rencana Anggaran Biaya Pekerjaan Pembangunan Pemecah Gelombang (Breakwater) Pantai Maligano, Desa Raimuna, Sulawesi Tenggara - Risdayatul Ningsi; Uniadi Mangidi; Januar Saleh Kaimuddin; Fathur Rahman Rustan (MEDIA KONSTRUKSI, 2024)
The Cost Budget Plan (RAB) is an estimate of the monetary value of an activity (project) that has taken into account the bestek drawings, work plans, wage lists, material price lists, analysis books, cost plan composition lists, and lists the amount of each type of work. The purpose of this study is to determine the total Budget Plan Cost (RAB) required on bending layer work, core layer work, main layer work, protective layer work, left-right foot protection work. The method used in this final project uses the water resources (SDA) method and uses the Excel 2010 application. The results of this study include the total cost budget of the main layer work Rp. 152,757.45, the total cost budget of the work on the main layer Rp. 611,809.15, the total cost of work on the protective layer Rp. 2,342,114.84, the total cost of work on the protective layer of left and right feet Rp. 611,809.16, and the total cost of work on earthworks amounted to Rp. 160,367.00. The total cost of work after being multiplied by the amount of 15% VAT on the construction of the 250 metre Maligano Beach Breakwater is Rp. 4,509,700,000, - (Four Billion Five Hundred Nine Million Seven Hundred Thousand Rupiah).